2020
DOI: 10.1007/s10143-020-01343-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and olfactory function after suprasellar craniopharyngioma surgery—a single-center experience comparing transcranial and endoscopic endonasal approaches

Abstract: The endoscopic endonasal approach to suprasellar craniopharyngiomas has become popular as alternative to transcranial approaches. However, the literature lacks data regarding quality of life and olfactory function. The assessment of the long-term quality of life and olfactory function of all patients harboring a suprasellar craniopharyngioma who underwent surgery in our department has been done. Patient characteristics and perioperative data were gathered in a prospectively maintained database. At the last fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
1
14
2
4
Order By: Relevance
“…The full-text articles of these 23 studies were then obtained. We excluded 15 studies including systematic reviews (n = 9), those with irrelevant outcomes (n = 3), and non-comparative studies (n = 3), leaving eight studies (376 patients) to be included in the final meta-analysis ( 3 , 4 , 16 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-text articles of these 23 studies were then obtained. We excluded 15 studies including systematic reviews (n = 9), those with irrelevant outcomes (n = 3), and non-comparative studies (n = 3), leaving eight studies (376 patients) to be included in the final meta-analysis ( 3 , 4 , 16 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using the Risk of Bias Assessment Tool for Non-randomized Studies system, the eight OS showed a low risk of bias in intervention measurement and blinding of outcome assessment and a high risk of bias in the selection of participants and confounding variables ( Supplementary Figure S2A ). Incomplete outcome data and selective outcome reporting were high risks of bias in two ( 20 , 21 ) and four studies ( Supplementary Figure S2B ) ( 4 , 16 , 20 , 21 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Awareness of these problems by the medical staff and family members may benefit the long‐term follow‐up and prognosis and should take it into mind when discussing treatment options and long‐term outcome with patients (Zhu et al, 2021 ). Psychological comfort, social support and effective rehabilitation guidance, detailed health education should be resorted to reduce the physical and psychological burden of patients with pituitary tumours (Dolci et al, 2021 ; Marx et al, 2021 ), and it is recognized that overwhelmingly avoided, resignated coping may make a negative impact on the disease, while appropriately guiding patients to take more active coping strategies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 23 ] In recent years, with the continuous application and development of EEA in craniopharyngioma patients, it has gradually replaced traditional craniotomy and is highly praised for its unique advantages such as less trauma and fewer postoperative complications. [ 24 27 ] Recurrent craniopharyngioma further increases the difficulty of surgery due to scar and adhesion after the previous operation, and the optimal surgical method is still controversial. EEA may be an effective and safe treatment method.…”
Section: Discussionmentioning
confidence: 99%